Administration of Lactobacillus johnsonii FI9785 to chickens affects colonisation by Campylobacter jejuni and the intestinal microbiota. Issue 4 (4th July 2017) - Mañes-Lázaro, R.; Van Diemen, P. M.; Pin, C.; Mayer, M. J.; Stevens, M. P.; Narbad, A.
ABSTRACT: 1. Campylobacter jejuni is the most common bacterial cause of human food-borne gastroenteritis in the world. A major source of human infection is the consumption of contaminated meat, particularly poultry. New control measures to reduce or eliminate this pathogen from the animal gastrointestinal tract are urgently required, and the use of probiotics as competitive exclusion agents is a promising biocontrol measure to reduce C . jejuni in the food chain. 2. In this study, we assessed the potential of Lactobacillus johnsonii FI9785, which has shown efficacy against Clostridium perfringens, to combat C . jejuni . The effect of prophylactic administration of L . johnsonii on the ability of C . jejuni to colonise chickens was determined. 3. Two doses of L . johnsonii given a week apart led to a reduction in C . jejuni colonisation in the caecal contents, but this biocontrol seemed reliant upon a high level of initial colonisation by the probiotic. 4. The microbial composition in the chicken gut was significantly altered by the probiotic treatment, as shown by denaturing gradient gel electrophoresis of 16S rRNA gene amplicons. 5. Together these results demonstrate the potential of this probiotic strain to be tested further as a competitive exclusion agent in poultry against C . jejuni .